Knowledge, beliefs, and attitudes of spinal manipulation: a cross-sectional survey of Italian physiotherapists - Firas Mourad; Marzia Stella Yousif; Filippo Maselli; Leonardo Pellicciari; Roberto Meroni; James Dunning; Emilio Puentedura; Alan Taylor; Roger Kerry; Nathan Hutting; Hendrikus Antonius Kranenburg (Chiropractic & Manual Therapies, 2022)
Abstract Background and Objective High-velocity low-amplitude thrust spinal manipulation (SM) is a recommended and commonly used manual therapy intervention in physiotherapy. Beliefs surrounding the safety and effectiveness of SM have challenged its use, and even advocated for its abandonment. Our study aimed to investigate the knowledge and beliefs surrounding SM by Italian physiotherapists compared with similar practitioners in other countries. Methods An online survey with 41 questions was adapted from previous surveys and was distributed via a mailing list of the Italian Physiotherapists Association (March 22–26, 2020). The questionnaire was divided into 4 sections to capture information on participant demographics, utilization, potential barriers, and knowledge about SM. Questions were differentiated between spinal regions. Attitudes towards different spinal regions, attributes associated with beliefs, and the influence of previous educational background were each evaluated. Results Of the 7398 registered physiotherapists, 575 (7.8%) completed the survey and were included for analysis. The majority of respondents perceived SM as safe and effective when applied to the thoracic (74.1%) and lumbar (72.2%) spines; whereas, a smaller proportion viewed SM to the upper cervical spine (56.8%) as safe and effective. Respondents reported they were less likely to provide and feel comfortable with upper cervical SM (respectively, 27.5% and 48.5%) compared to the thoracic (respectively, 52.2% and 74.8%) and lumbar spines (respectively, 46.3% and 74.3%). Most physiotherapists (70.4%) agreed they would perform additional screening prior to upper cervical SM compared to other spinal regions. Respondents who were aware of clinical prediction rules were more likely to report being comfortable with SM (OR 2.38–3.69) and to perceive it as safe (OR 1.75–3.12). Finally, physiotherapists without musculoskeletal specialization, especially those with a traditional manual therapy background, were more likely to perform additional screening prior to SM, use SM less frequently, report being less comfortable performing SM, and report upper cervical SM as less safe (p < 0.001). Discussion The beliefs and attitudes of physiotherapists surrounding the use of SM are significantly different when comparing the upper cervical spine to other spinal regions. An educational background in traditional manual therapy significantly influences beliefs and attitudes. We propose an updated framework on evidence-based SM.